2015
DOI: 10.1115/1.4029580
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Platelet Activation Potential in Abdominal Aortic Aneurysms

Abstract: Intraluminal thrombus (ILT) in abdominal aortic aneurysms (AAA) has potential implications to aneurysm growth and rupture risk; yet, the mechanisms underlying its development remain poorly understood. Some researchers have proposed that ILT development may be driven by biomechanical platelet activation within the AAA, followed by adhesion in regions of low wall shear stress. Studies have investigated wall shear stress levels within AAA, but platelet activation potential (AP) has not been quantified. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 60 publications
1
34
0
Order By: Relevance
“…Since its initial release, SimVascular has contributed to numerous advances in fundamental disease research, surgical planning, and medical device design [30,[45][46][47][48][49][50][51][52][53][54][55]. An accompanying publicly available data repository 4 provides patient-specific image data, models, and simulation results of over 120 clinical cases from different regions of the vasculature, including cerebrovascular, coronary, aortofemoral, pulmonary, and congenital heart disease [33,56,57].…”
Section: Introductionmentioning
confidence: 99%
“…Since its initial release, SimVascular has contributed to numerous advances in fundamental disease research, surgical planning, and medical device design [30,[45][46][47][48][49][50][51][52][53][54][55]. An accompanying publicly available data repository 4 provides patient-specific image data, models, and simulation results of over 120 clinical cases from different regions of the vasculature, including cerebrovascular, coronary, aortofemoral, pulmonary, and congenital heart disease [33,56,57].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism that leads thrombus accumulation are still not well understood; While it is still uncertain whether platelets are mechanically activated 4 , or biochemical induced 23 , it is known that hemodynamic forces play an important role. Doyle and colleagues 11 , by using a patient-specific geometry of one patient observed that the regions where the AAA expanded coincided with the regions of low TAWSS and ILT accumulation, which in turn was the same area that experienced ruptured.…”
Section: Introductionmentioning
confidence: 99%
“…As PAS, which represents the current state of platelet activation in Equation (), could not be initially zero, a non‐zero background level of activation for each platelet was required. A background level of 1%–20% could be used for this purpose . In the present study, to validate the numerical results against the experimental results presented by Yin et al, a background level of 1% was used as suggested by Hedayat et al because Yin et al employed apheresis units of platelets with no initial activation.…”
Section: Methodsmentioning
confidence: 82%
“…For all other simulations, a background level of 20% was employed. The purpose of using a high background level of 20% for all simulations was to incorporate the effect of multiple cardiac cycles that a platelet passes through BMHV during its lifetime as only 1 cardiac cycle was simulated in this study …”
Section: Methodsmentioning
confidence: 99%